2014
DOI: 10.3332/ecancer.2014.492
|View full text |Cite
|
Sign up to set email alerts
|

The current situation in education and training of health-care professionals across Africa to optimise the delivery of palliative care for cancer patients

Abstract: The need for palliative care education remains vital to contribute to the quality of life of patients, both adults and children, with cancer in Africa. The number of patients with cancer continues to rise, and with them the burden of palliative care needs. Palliative care has been present in Africa for nearly four decades, and a number of services are developing in response to the HIV/AIDS epidemic. However, the needs of cancer patients remain a challenge. Education and training initiatives have developed thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 31 publications
3
33
0
Order By: Relevance
“…The finding on lack of well trained counselors in this study supportsRawlinson, Gwyther [18], who identified lack of proper palliative care training among health care providers in Africa.…”
Section: Discussionsupporting
confidence: 82%
“…The finding on lack of well trained counselors in this study supportsRawlinson, Gwyther [18], who identified lack of proper palliative care training among health care providers in Africa.…”
Section: Discussionsupporting
confidence: 82%
“…Malawi was the first African country to have a specifically paediatric palliative care service (Knapp et al, 2012) (Rawlinson et al, 2014).…”
Section: Challenges Of Cancer Care In Lmicsmentioning
confidence: 99%
“…Uganda, South Africa and a few other countries have distance learning degree courses in palliative care. (Rawlinson et al, 2014).…”
Section: Challenges Of Cancer Care In Lmicsmentioning
confidence: 99%
“…Stjernsward et al, (2007) suggested that Governments in developing countries needed to include palliative care in the National Health Plan and devise a mechanism for funding and/or service delivery models that support service delivery [2]. Unfortunately, most countries in Africa including Zambia have not yet included palliative care in their national policies or regulations [3,4,[19][20][21][22].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Lack of national standard operating procedures, guidelines and treatment protocols for PC were also observed as a challenge in implementing of the service. [3,4,[19][20][21][22]. Therefore, lack of national PC guidelines usually results in PC not being included in the national health system.…”
Section: Lack Of Pc Guidelinesmentioning
confidence: 99%